KESEDIAAN MEMBAYAR LEBIH TERHADAP BERAS ORGANIK DI TRANSMART ICONMALL GRESIK - Nellasari, Arinda Dwi; Nugroho, Sigit Dwi; Nurhadi, Eko (Berkala Ilmiah AGRIDEVINA, 2020)
Public awareness of a healthy lifestyle makes organic products in great demand, including organic rice. The willingness to pay consumers for a good or service is determined by the desire of each individual or household who tries to maximize is utility with certain income and will determine the amount of demand for goods or services to be consumed. Therefore, it is necessary to do research on the factors that affect the willingness to pay consumers for organic rice. The research was conducted at Iconmall Gresik Transmart. The sample of this research was 40 people with the criteria that they had bought at least once organic rice products and were at least 17 years old. The data used in this research include primary data and secondary data. Data analysis used is contingent valuation analysis. The results showed that organic rice consumers are willing to pay more for all types of organic rice brands sold on Iconmall Gresik Transmart, where the total average for the type of Hotel Beras Kepala Super brand is Rp 33.214,286, Pure Green Pandan Wangi is Rp 41.444,445, Hotel Beras Merah Premium is Rp 36.181,817, dan Tropicana Slim Panino is Rp 39.096,001. DOI : https://doi.org/10.33005/adv.v9i2.2460